Šolski esej in splošna matura iz slovenščine - Ambrož, Darinka (Jezik in slovstvo, 2015)
The development of the school essay as part of the General Matura in Slovenian language is closely related to the development of the didactics of literature founded by Boža Krakar Vogel. In the last two decades, the instructions for writing the essay, the method of its grading, and the number of prescribed literary works have changed, while the prudent selection of the thematic headings has remained a constant. Further development of the school essay in the General Matura is an important and demanding task that requires co-ordinated professional efforts on the part of academics in the area of literature and the didactics of literature, as well as on the part of experts from the National Education Institute of the Republic of Slovenia and the examination committee for Slovenian language, which has benefitted from staff reinforcement, acting within the framework of the National Examinations Centre.
Keywords: Krakar Vogel, Boža, 1950-; didaktika književnosti; Slovene; slovenščina; splošna matura; šolski esej